Screening and topical decolonization of preoperative nasal Staphylococcus aureus carriers to reduce the incidence of postoperative infections after lung cancer surgery: a propensity matched study. (30th December 2019) - Fourdrain, Alex; Bouabdallah, Ilies; Gust, Lucile; Cassir, Nadim; Brioude, Geoffrey; Falcoz, Pierre-Emmanuel; Alifano, Marco; Le Rochais, Jean-Philippe; D'Annoville, Thomas; Trousse, Delphine; Loundou, Anderson; Leone, Marc; et al.
Abstract: : OBJECTIVES: Health care-associated infections (HAIs) are serious issues following lung cancer surgery, leading to an increased risk of morbidity and hospital cost burden. The aim of this study was to evaluate the impact on postoperative outcomes of a preoperative screening and decolonization strategy of nasal carriers for Staphylococcus aureus prior to lung cancer surgery. METHODS: We performed a retrospective study comparing 2 cohorts of patients undergoing major lung resection: a control group of patients from the placebo arm of the randomized Clinical Study to Evaluate the Efficacy of Chlorhexidine Mouthwashes operated on between July 2012 and April 2015 without any nasopharyngeal screening ( N = 224); an experimental group, with preoperative screening for S. aureus of nasal carriers and selective 5-day decolonization in positive carriers using mupirocin ointment between January 2017 and December 2017 ( N = 310). The 2 groups were matched according to a propensity score analysis with 1:1 matching. The primary outcome was the rate of postoperative HAIs, and the secondary outcome was the need for postoperative mechanical ventilation after surgery. RESULTS: After matching, 2 similar groups of 108 patients each were obtained. In the experimental group, 26 patients had positive results for nasal carriage, and a significant decrease was observed in the rate of overall postoperative HAIs [control n = 19, 17.6%; experimental group n = 9, 8.3%; P = 0.043; relative risk 0.47 (0.22–1)] and in the rate of postoperative mechanical ventilation [control n = 12, 11.1%; experimental group n = 4, 3.7%; P = 0.038; relative risk 0.33 (0.11–1)]. After logistic regression and multivariable analysis, screening of S. aureus nasal carriers reduced the rate of HAIs [odds ratio (OR) 0.29, 95% confidence interval (CI) 0.11–0.76; P = 0.01] and reduced the risk of the need for postoperative mechanical ventilation (OR 0.19, 95% CI 0.05–0.74; P = 0.02). There was no significant statistical difference between the 2 groups regarding the rate of postoperative S. aureus -associated infection (control group n = 6, 5.6%; experimental group n = 2, 1.9%; P = 0.28). CONCLUSIONS: Identification of nasal carriers of S. aureus and selective decontamination using mupirocin appeared to have a beneficial effect on postoperative infectious events after lung resection surgery.